Image Processing Based Scrub Tester Design and Production - Serdar Kaçamer; Mehmet Budakçi; Ferzan Katırcıoğlu (Drvna Industrija)
Determining how resistant paint, varnish or coating type materials, applied to wood-based panel surfaces, are to the effects of exposure to household chemicals is important in terms of developing products and providing durable surface coating to users. Every paint or coating type product coming off the production line needs to be tested quickly, and a new direction should be given to the work based on the positive or negative results obtained. Products without quality monitoring are returned by customers due to insufficient performance, resulting in loss of time, labor and materials. In this study, an Image Processing Based Scrub Tester (IPBST) was designed and produced in order to imitate the effect of paint, varnish and coating materials on the surfaces of furniture and decoration elements used in daily life against household chemicals. Unlike its counterparts, with IPBST, the image of each sample is digitally recorded before and after the scrubbing process, thanks to the “compact photo booth” integrated into the device. Wear, color and brightness change analyses of sample images can be performed with the “Surface Flaw Analysis (SFA)” method developed using the Matlab Graphical User Interface (GUI) image processing program on a computer integrated into the device. In this way, a 4-in-1 device that can do the job of 4 devices has been provided to the relevant scientific community and industry without the need for different types of industrial test devices.